Kajian Sejarah Aktivitas Dakwah dan Pendidikan di Indonesia (Tsamratul Fikri | Jurnal Studi Islam, 2022)
The history of da'wah and Islamic education in Indonesia is closely related to Islamic history so that the periodization of the history of Islamic education is in several periods of Islamic history itself including the old, middle and new periods. In Indonesia, this period can be grouped into: the phase of the entry of Islam, the phase of the development and establishment of the Islamic empire, the phase of the arrival of foreigners, the colonial phase, the phase of independence, and the phase after independence. In each of these phases, da'wah and Islamic education develop with different characteristics. Even so, in every phase of the development of da'wah and Islamic education. The color of da'wah and education is always attached to and functions to maintain and transform Islamic values in the implementation of da'wah and education in Indonesia.